PERLINDUNGAN "HAK SPIRITUAL" DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH: PRAKTIK DI MALAYSIA DAN INDONESIA - Rof'ah Setyowati (Share: Jurnal Ekonomi dan Keuangan Islam, 2016)
"Spiritual right" is the right in the spiritual aspect that is owned by any person. The Spirituality of Muslim customers is influenced by sharia principles in various aspects of their lives. The protection against "spiritual right" is also required in the settlement of disputes between customers and Islamic banking institution. Indonesian regulation has provided the foundation for the protection of the spiritual rights. The issuing of the MK (Constitutional Court)'s verdict Number 93/PUU-X/2012, can also lead to that purpose. However, there is still a "spiritual right" post the verdict. This study utilizes two types of joint research method called socio-legal research. It employs several approaches, namely philosophical, historical, critical, analytical, comparative, and so on. However, the most prominently used is the comparative approach as it is associated with the purpose of this study in digging Malaysian experiences with its longer period of having various legal problems. It is hoped that these experiences can be referred to as a pattern for more effective "spiritual right". The analysis shows that the effectiveness of the "spiritual right" protection in settling the dispute of Islamic banking institutions is dominantly influenced by the policy of financial services authority, which in Malaysia is Bank Negara Malaysia (BNM) and Otoritas Jasa Keuangan (OJK) in Indonesia. ========================================================================================================"Hak spiritual" merupakan hak dalam aspek spiritual yang dimiliki oleh setiap orang. Spiritulitas konsumen Muslim dipengaruhi oleh prinsip-prinsip syariah dalam berbagai aspek kehidupannya. Perlindungan terhadap "hak spiritual" juga dibutuhkan dalam penyelesaian sengketa antara nasabah dengan institusi perbankan syariah. Melalui peraturan perundangan, telah diberikan landasan bagi perlindungan "hak spiritual". Munculnya Putusan MK Nomor 93/PUU-X/2012, hakekatnya juga mengarah pada maksud tersebut. Namun permasalahannya, pasca putusan MK tersebut, masih terdapat "hak spiritual". Kajian ini menggunakan dua jenis penelitian gabungan, yang disebut dengan socio-legal research. Beberapa metode pendekatan dilakukan, antara lain: filosofis, historis, analitis kritis, dan komparatif. Namun yang paling menonjol digunakan ialah metode komparatif. Penggunaan metode ini dikaitkan dengan tujuan kajian ini untuk mengambil pengalaman dari Malaysia yang lebih lama dengan berbagai problematika hukum yang ada, untuk manjadi acuan guna mendapatkan pola perlindungan "hak spiritual" yang lebih efektif. Hasil analisis ini menujukkan bahwa efektifitas perlindungan "hak spiritual" dalam penyelesaian sengketa perbankan syariah sangat dipengaruhi oleh kebijakan lembaga pemegang otoritas pembinaan, pengawasan dan pengaturan perbankan syariah. Dalam konteks ini, di Malaysia ialah BNM, sementara di Indonesia ialah OJK.